The Students' Engagement in EFL Online Class - Susanti, Yunik (Lingual Journal of Language and Culture, 2020)
A closed-ended questionnaire was designated to the English Department students University of Nusantara PGRI Kediri to investigate their cognitive, behavioural and emotional engagement during the English teaching learning processes that were administered in online classes. These online classes were managed to implement the government policy in banning the spread of the Covid-19 pandemic. The results showed that the students’ behavioural engagement was relatively high, however, their cognitive and emotional engagement were not extensively positive in some of their aspects. It was found that the students found obstacles in communicating ideas, helping each other, previewing the previous materials, and overcoming anxiety in making mistake during the online class. The findings contributes to an understanding of the various aspects of web-based classes and the EFL students’ engagement in the virtual classes. .